2018
DOI: 10.21037/jtd.2018.03.79
|View full text |Cite
|
Sign up to set email alerts
|

Total arch replacement and frozen elephant trunk for type A aortic dissection after Bentall procedure in Marfan syndrome

Abstract: Background: We seek to report the long-term outcomes of the total arch replacement and frozen elephant trunk (TAR + FET) technique for type A aortic dissection (TAAD) following prior Bentall procedure in patients with Marfan syndrome (MFS). Methods: Between 2003 and 2015, we performed TAR + FET for 26 patients with MFS who developed TAAD following a prior Bentall procedure. Mean age at FET 36.9±9.7 years and 24 were males. TAAD was acute in 8 (30.8%, all new dissections from precious root aneurysm) and chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(73 reference statements)
1
6
0
Order By: Relevance
“…According to the 2014 European Society of Cardiology guidelines, aortic dissection is divided into sub-acute (15-90 days) and chronic (>90 days) (1). Patients with cTAAD who had a history of proximal aortic surgery were excluded from this study (10,15). The diagnosis of cTAAD was confirmed by computed tomographic angiogram (CTA) in all patients.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the 2014 European Society of Cardiology guidelines, aortic dissection is divided into sub-acute (15-90 days) and chronic (>90 days) (1). Patients with cTAAD who had a history of proximal aortic surgery were excluded from this study (10,15). The diagnosis of cTAAD was confirmed by computed tomographic angiogram (CTA) in all patients.…”
Section: Patientsmentioning
confidence: 99%
“…Since 2003, we have been using the TAR and FET technique to repair TAAD for patients with MFS (8). Our experience has proven the benefits of the TAR and FET technique with respect to long-term survival and freedom from reoperation in such patients (7,(9)(10)(11)(12). In this study, we seek to assess the early and long-term outcomes of the TAR and FET technique for cTAAD in MFS, and to identify the risk factors for death and reoperation in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although operation on the great artery can currently be done by many hospitals in China, primary hospitals conduct ascending aortic replacement or root replacement instead of more thorough surgical methods only for patients with acute type A aortic dissection, due to technical conditions and hardware factors, which will lead to reoperation in the future. The literature has reported that the 5-year survival rate for type A AD patients receiving simple ascending aortic replacement or root replacement for the first time is only 70–80%, the 10-year reoperation rate is more than 10% [69], and the average age of Chinese patients is around 45 years old. These results are unacceptable, since the average age of the patients in this study was 44.7 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The indication of TAR + FET for TAAD in MFS patients was DeBakey type I dissection, as well as DeBakey type II dissection with an enlarged arch or proximal descending aorta. The surgical technique of TAR + FET has been depicted in detail previously (6,10,11).…”
Section: Patients and Follow-upmentioning
confidence: 99%